2022
DOI: 10.3389/fimmu.2022.748839
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Abundance, and Virulence of Adherent-Invasive Escherichia coli in Ulcerative Colitis, Colorectal Cancer, and Coeliac Disease

Abstract: Background & AimsAdherent-invasive E. coli (AIEC) has largely been implicated in the pathogenesis of Crohn’s disease (CD). E. coli strains with similar genetic backgrounds and virulence genes profiles have been associated with other intestinal disorders, such as ulcerative colitis (UC), colorectal cancer (CRC), and coeliac disease (CeD), but the role of AIEC in these diseases remains unexplored. We aimed to assess the distribution, abundance, and pathogenic features of AIEC in UC, CRC, and CeD.MethodsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…A recent study found that all AIEC strains isolated from UC and CRC belonged to the B1 phylogroup (except for a strain of the A phylogroup), compared to the CeD cohort which had none of the isolated E. coli being AIEC. 114 This implicates the integration of strain-specific microbial profiles in differentiating IBD from other gastrointestinal conditions. Other reports reveal that Clostridium spp., Prevotella spp ., and Actinomyces spp .…”
Section: Discriminatory Potentials Of Gut Bacteriamentioning
confidence: 95%
See 1 more Smart Citation
“…A recent study found that all AIEC strains isolated from UC and CRC belonged to the B1 phylogroup (except for a strain of the A phylogroup), compared to the CeD cohort which had none of the isolated E. coli being AIEC. 114 This implicates the integration of strain-specific microbial profiles in differentiating IBD from other gastrointestinal conditions. Other reports reveal that Clostridium spp., Prevotella spp ., and Actinomyces spp .…”
Section: Discriminatory Potentials Of Gut Bacteriamentioning
confidence: 95%
“… Sample source Study type/focus Study subject Analytical technology Bacteria involved Key findings Reference Biopsy Population-based case-control CD and UC RISA followed by DNA sequencing B2 + D phylogenetic E. coli More prevalent in patients with UC and CD than controls 94 Biopsy and fecal Prevalence of AIEC in selected cohorts UC, CRC, CeD Culture and identification E. coli No AIEC found in CeD. AIEC prevalence higher in CD: 55.0% than CD with colonic disease: 40.0% and UC: 35.7% 114 Fecal Characterizing isolated E. coli strains IBD and healthy controls Culture and identification E. coli strains Phylogenetic group B2 E. coli are frequent in IBD involving the left side of the colon. B2 strains with ExPEC genes are more frequent in active IBD than inactive IBD 95 Fecal Case-control analysis UC, CD, IBS UC and healthy controls Shotgun metagenomic sequencing Bacteroides uniformis and Bifidobacterium bifidum Faecalibacterium prausnitzii Escherichia/Shigella species 15 UC-specific associations, including Bacteroides uniformis and Bifidobacterium bifidum Decreased in UC compared to controls Increased in CD 11 Fecal Cross-sectional IBD and healthy controls 16S rRNA gene sequencing Proteobacteria ( Shigella/Escherichia ), Firmicutes, specifically F. prausnitzii , and Bacteroidetes ( Bacteroides and Prevotella ) Diagnostic rate ...…”
Section: Prognostic Potentialsmentioning
confidence: 99%
“…The number of C. plasmodium in the feces of UC patients was reported to be decreased. Due to the different proportions of C. plasmodium and E. coli in ileal and colonic CD, this ratio can be considered a promising biomarker for differential diagnoses and personalized treatments[ 88 ].…”
Section: Aiec In CDmentioning
confidence: 99%
“…This region of the intestine contains absorptive enterocytes, mucin secreting goblet cells, and M-like cells, all of which are also found in the mammalian small intestine (49). Accordingly, AIEC predominantly colonizes the mammalian small intestine compared to the colon of IBD patients (3, 50-52).…”
Section: Discussionmentioning
confidence: 99%